The modern contract of guarantee - Courtney, Wayne; Phillips, John C.; O'Donovan, James; Phillips, John C. (London : Thomson Reuters/Sweet & Maxwell, 2016)
"The Modern Contract of Guarantee provides readers with a detailed reference work on the law of guarantees. The authors provide practical insights into areas such as the validity and construction of guarantees, how to avoid a guarantee being discharged and common difficulties with enforcement. The authors also provide drafting guidance and a useful comparative discussion of developments in England and Commonwealth countries." --Publishers website.
Preface -- Table of Cases -- Table of Statutes -- Table of Rules and Statutory Instruments -- Table of EU Legislation -- Table of Conventions -- Part I. Formation and Validity : -- 1. Definition and Distinctions -- 2. Formation of the Contract of Guarantee -- 3. Formal Requirements -- 4. Factors Affecting Validity -- Part II. Liability and Discharge : -- 5. The Scope of the Guarantor's Liability -- 6. Discharge from Liability by the Determination of the Principal Transaction -- 7. Discharge from Liability by Reason of the Creditor's Conduct towards the Principal -- 8. Discharge from Liability by Reason of the Conduct in Relation to the Guarantor -- 9. Discharge from Liability by the Determination of the Guarantee -- Part III. The Rights of the Parties : -- 10. Rights of the Creditor -- 11. Rights of the Guarantor before Payment -- 12. Rights of the Guarantor after Payment -- Part IV. Guarantees in Particular Contexts : -- 13. Performance Bonds -- 14. Suretyship in Private International Law -- Index.
Includes bibliographical references and index.
1 2
Keywords: Suretyship and guaranty -- Australia; Suretyship and guaranty; Suretyship and guaranty; Australia; 86.11 comparative law; 86.27 commercial law; 86.26 law of obligations; EU countries; Australia